Implementasi Model Missouri Mathematics Project (MMP) Berbantuan Media Untuk Meningkatkan Kemampuan Berpikir Kritis Dan Kolaborasi Siswa - Aeni, Nurul; Fatkhiyani, Kiki; Khoimatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by students' statements that mathematics is a difficult subject and the lack of enthusiasm of students in participating in the learning process. Based on these problems, this classroom action research aims to apply the Missouri Mathematics Project (MMP) model assisted by geoboard media to improve students' critical thinking and collaboration skills in mathematics subjects for grade IV students of SDN 2 Pringgacala. The subjects of the research were grade IV students of SDN 2 Pringgacala in the 2024/2025 school year with a total of 37 students. This research was conducted in 3 cycles consisting of 4 stages in each cycle, namely planning, action, observation and reflection. Data collection techniques used in this study include observation and testing. The data collection instruments used were observation sheets and test questions. The results of this study indicate that the results of the application of the Missouri Mathematics Project (MMP) model in cycle I obtained an average score of 3.7 then in cycle II it increased to 3.8 and in cycle III it increased again to 3.9. The improvement of students' critical thinking skills can be seen in cycle I obtaining an average score of 76 then in cycle II it increased to 83 and in cycle III it increased again to 86. The improvement of students' collaboration skills can be seen in cycle I obtaining an average score of 3.28 then in cycle II it increased to 3.45 and in cycle III it increased again to 3.6. Based on the results of the study, it can be concluded that the implementation of the Missouri Mathematics Project (MMP) model assisted by geoboard media can improve students' critical thinking and collaboration skills